Implementation Of Public Relations Management In Building Public Trust At Luqman Al-Hakim Primary School In Jember - Shibghatallaah Mujaahid Al Islaam; Riayatul Husnan (The Faculty of Education and Teaching Training, 2023)
Public Relations Management (PR) in educational institutions has an important role and function in building and maintaining relations betwe institutions and the community, so as to provide public trust and influence the success of these institutions. SD Luqman Al Hakim Jember was chosen because of the many public relations programs that other schools do not have. This study aims to describe the Planning, Implementation and Evaluation of Public Relations Management Implementation in Building Public Trust at SD Luqman Al Hakim Jember. The research method uses a descriptive qualitative approach with a phenomenological research type using interview techniques, observation and documentation. Data analysis in this study was carried out by collecting data, condensing data, presenting data, drawing conclusions and verifying. To ensure the validity of the data using data and source triangulation techniques. The results of the research are: 1) HUMAS management planning is carried out during a work meeting at the beginning of the year which takes into account the results of the HUMAS work evaluation in the previous year. 2) the implementation of Public Relations Management is carried out online by maximizing the school website and then also carried out offline in the form of holding routine activities which are attended by student parents. 3) Evaluation of HUMAS management is carried out through year-end meetings or incidental HUMAS activity evaluation meetings. Manajemen Hubungan Masyarakat (HUMAS) pada Lembaga Pendidikan memiliki peranan dan fungsi penting dalam membangun dan mempertahankan hubungan antara lembaga dan masyarakat, sehingga dapat memberikan kepercayaan public dan perngaruh kesuksesan terhadap lembaga tersebut. SD Luqman Al Hakim Jember dipilih karena banyaknya program humas yang tidak dimiliki pada sekolah lain. Penelitian ini bertujuan untuk mendeksipsikan Perencanaan, Pelaksanaan dan Evaluasi Implementasi Manajemen HUMAS dalam Membangun Kepercayaan Publik di SD Luqman Al Hakim Jember. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian fenomenologis menggunakan teknik wawancara, observasi dan dokumentasi. Analisis data pada penelitian ini dengan melakukan pengumpulan data, kondensasi data, penyajian data, penarikan kesimpulan dan verifikasi. Untuk menjamin keabsahan data menggunakan teknik triangulasi data dan sumber. Hasil Penelitian menyimpulkan bahwa: 1) perencanaan manajemen HUMAS dilakukan pada saat rapat kerja awal tahun yang mempertimbangkan hasil evaluasi kerja HUMAS di tahun sebelumnya. 2) pelaksanaan Manajemen HUMAS dilakukan secara online dengan memaksimalkan website sekolah kemudian juga dilakukan secara offline dalam bentuk mengadakan kegiatan rutin yang diikuti wali murid. 3) Evaluasi manajemen HUMAS dilakukan melalui rapat akhir tahun ataupun rapat evaluasi kegiatan Humas yang berupa insidental.